2017
DOI: 10.1242/jcs.196790
|View full text |Cite
|
Sign up to set email alerts
|

The Aurora-A–Twist1 axis promotes highly aggressive phenotypes in pancreatic carcinoma

Abstract: We uncovered a crucial role for the Aurora kinase A (AURKA)-Twist1 axis in promoting epithelial-to-mesenchymal transition (EMT) and chemoresistance in pancreatic cancer. Twist1 is the first EMT-specific target of AURKA that was identified using an innovative screen. AURKA phosphorylates Twist1 at three sites, which results in its multifaceted regulation -AURKA inhibits its ubiquitylation, increases its transcriptional activity and favors its homodimerization. Twist1 reciprocates and prevents AURKA degradation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 42 publications
3
63
0
1
Order By: Relevance
“…Again, it would be interesting to explore whether these events require the prior activation of AURKA on AURKA was also shown to play an active role in the Epithelial-Mesenchimal transition (EMT) in oestrogen receptor -positive breast cancer models [119], and in models of pancreatic cancer [120,121].…”
Section: Interphase Aurka Is Involved In Cell Migration and Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, it would be interesting to explore whether these events require the prior activation of AURKA on AURKA was also shown to play an active role in the Epithelial-Mesenchimal transition (EMT) in oestrogen receptor -positive breast cancer models [119], and in models of pancreatic cancer [120,121].…”
Section: Interphase Aurka Is Involved In Cell Migration and Invasionmentioning
confidence: 99%
“…However, the molecular mechanism by which AURKA induces EMT remains to be fully disclosed. Two parallel studies identified two direct substrates of AURKA implicated in pancreatic EMT programs, aldehyde dehydrogenase 1 (ALDH1A1) [120] and Twist-related protein 1 (TWIST1) [121]. The AURKA-dependent phosphorylation of both proteins increases their respective enzymatic activity, with a dramatic enhancement of cell motility, drug resistance and the acquisition of a stem-like phenotype.…”
Section: Interphase Aurka Is Involved In Cell Migration and Invasionmentioning
confidence: 99%
“…Hypo-phosphorylation mutations (T121A, S123A) near or at the Helix I phosphorylation sites was previously shown to favour homodimerization (Firulli et al, 2005). Yet a triple phospho-mutant model of TWIST1 (S123A, T148A and A184A) in oncogenic cell lines showed preference for dimerization with TCF3 and HAND2 compared to wildtype TWIST1 (Wang et al, 2017). In line with this, we find that two individual hypo-phosphorylation mutants (R118H, S123A) both increased preference for TCF12 heterodimer formation, whilst phospho-mimetic forms at T121 and S123 reduced heterodimerization, compared to wildtype TWIST1.…”
Section: Molecular Pathology Of Scs Mutations In Context Of Bhlh Factmentioning
confidence: 97%
“…We have identified many substrates of Cdk5‐as1/p25 in mouse brain lysates, which uncovered several molecular mechanisms by which deregulated Cdk5 promotes neurodegenerative pathways in Alzheimer's disease pathogenesis . Similarly, this approach revealed oncogenic targets of Aurora A kinase in breast and pancreatic cancer, which unraveled the mechanism of Aurora A‐induced epithelial to mesenchymal transition and cancer stem cell formation in highly aggressive cancers . As such, the ASKA method represents a powerful tool for identifying kinase‐specific substrates.…”
Section: Direct Tagging Of Kinase Substratesmentioning
confidence: 98%
“…Despite two mutations in the active site, both Aurora A‐as7 and Aurora B‐as7 are highly active in cells and in vitro; and show very high catalytic efficiency with N‐6‐phenethyl ATP analog. Using Aurora A‐as7 kinase, we have identified several direct targets including PHLDA1, LIMK2, ALDH1A1, and TWIST1 in cell lysates .…”
Section: Direct Tagging Of Kinase Substratesmentioning
confidence: 99%